The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40364-022-00359-3
|View full text |Cite
|
Sign up to set email alerts
|

Donor T cells for CAR T cell therapy

Abstract: Adoptive cell therapy using patient-derived chimeric receptor antigen (CAR) T cells redirected against tumor cells has shown remarkable success in treating hematologic cancers. However, wider accessibility of cellular therapies for all patients is needed. Manufacture of patient-derived CAR T cells is limited by prolonged lymphopenia in heavily pre-treated patients and risk of contamination with tumor cells when isolating T cells from patient blood rich in malignant blasts. Donor T cells provide a good source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 123 publications
0
6
0
Order By: Relevance
“…The CAR T-ddBCMA product, utilizing a novel synthetic binding domain, called D-Domain, demonstrated an ORR of 100% (≥VGPR 88%) after a median follow up of approximately 10 months [ 150 ]. Allogenic CAR T-cell products generated from T-cells of healthy donors have also been clinically assessed with promising outcomes and acceptable AE profiles; however, they have not been approved for clinical use yet [ 151 , 152 ]. These might be a good option for patients requiring prompt treatment and who cannot wait for the time-consuming manufacture of autologous CAR T-cells.…”
Section: Available Therapeutic Modalitiesmentioning
confidence: 99%
“…The CAR T-ddBCMA product, utilizing a novel synthetic binding domain, called D-Domain, demonstrated an ORR of 100% (≥VGPR 88%) after a median follow up of approximately 10 months [ 150 ]. Allogenic CAR T-cell products generated from T-cells of healthy donors have also been clinically assessed with promising outcomes and acceptable AE profiles; however, they have not been approved for clinical use yet [ 151 , 152 ]. These might be a good option for patients requiring prompt treatment and who cannot wait for the time-consuming manufacture of autologous CAR T-cells.…”
Section: Available Therapeutic Modalitiesmentioning
confidence: 99%
“…Off-the-shelf CAR T-cells are newly developed universal allogeneic CAR T-cells where T-cells are collected from healthy donors. This ensures that a good number of healthy T-cells are retrieved and, unlike autologous CAR T-cells, are not affected by chemotherapy or cancer cells [117,118]. It was suggested that CAR T-cells performance could be greatly affected by the quality and quantity of retrieved T-cells [53,119].…”
Section: Future Prospects For Car T-cell Therapy In the Treatment Of Allmentioning
confidence: 99%
“…It allows the patient to have immediate access to the treatment. There is no need to wait for the 3-week interval which is usually required to manufacture personalized autologous CAR T-cells [115,118]. The term (FasTCAR) is gaining popularity and is used to indicate the next-day manufacturing of CAR T-cells using novel manufacturing platforms.…”
Section: Future Prospects For Car T-cell Therapy In the Treatment Of Allmentioning
confidence: 99%
“…Therefore, it has been widely adopted for alloCAR-T cells. Justin Eyquem et al first targeted a CAR to the TRAC locus with CRISPR/Cas9 and enhanced its tumor elimination ability compared to traditional CAR-T [ 143 , 144 ]. Subsequently, Xiaojuan Liu et al verified that CRISPR/Cas9 mediated editing of TRAC and B2M is readily applicable to alloCAR-T cells [ 145 ].…”
Section: Strategies For Enhancing Car-t Cell Function By Genetic Mani...mentioning
confidence: 99%